Dalam, yang STRATEGI PENGANGGARAN PENDIDIKAN ISLAM DALAM MEWUJUDKAN MANAJEMEN KEUANGAN YANG PROFESIONAL - Salsabila, Nurul Adilla; Nursita, Lisa (Educational Leadership: Jurnal Manajemen Pendidikan, 2026)
Educational financial management is a strategic process in organizing, administering, and supervising all financial activities of educational institutions sourced from the government, the community, and other legitimate sources. This article aims to examine the principles, regulations, and implementation of Islamic educational financial management with an emphasis on transparency, accountability, effectiveness, efficiency, and balance. The research uses a desk study method through analysis of literature, journals, and relevant laws and regulations. The results of the study indicate that Islamic educational financial management is not only administrative but also has social, humanitarian, and spiritual dimensions. Regulations such as the National Education System Law, the Government Regulation on Religious Education, and the Islamic Boarding School Law serve as the legal basis for Islamic education funding. Funding sources come from the National Budget (APBN), Regional Budget (APBD), the community, zakat, waqf, and grants, which must be managed in accordance with sharia principles. The Qur'an emphasizes justice and prohibits usury, gharar, and maisir. The application of these principles can improve service quality, expand access to education, and build a generation with morals and competitiveness.